2015
DOI: 10.1039/c4ce02044h
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical cocrystals of the anti-tuberculosis drug pyrazinamide with dicarboxylic and tricarboxylic acids

Abstract: Four cocrystals of the anti-tuberculosis drug pyrazinamide (PZA) with adipic acid (1), sebacic acid (2), trans-aconitic acid (3), and citric acid (4) were successfully designed and synthesised. Their structures were determined by single-crystal X-ray diffraction, in which 1 and 2 displayed one-dimensional chain structures, while 3 and 4 formed two-dimensional hydrogen bonded frameworks between PZA and the coformers. The equilibrium solubility and intrinsic dissolution rate (IDR) of the four cocrystals and PZA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…The anti-tuberculosis pharmaceuticals pyrazinamide (PYR) and ethionamide (ETH) are structurally similar and comprise both hydrogen-bond donor and acceptor sites. The ability of the drugs to form multiple hydrogen bonds [ 65 , 66 ] makes them synthetically and structurally intriguing. The API PYR contains an amide and two aromatic nitrogen atoms as synthon handles ( figure 8 a ), and is frequently used in combination with other drugs, which can pose compatibility and bioavailability issues [ 65 ].…”
Section: Co-crystals Involving Pharmaceutical Compoundsmentioning
confidence: 99%
“…The anti-tuberculosis pharmaceuticals pyrazinamide (PYR) and ethionamide (ETH) are structurally similar and comprise both hydrogen-bond donor and acceptor sites. The ability of the drugs to form multiple hydrogen bonds [ 65 , 66 ] makes them synthetically and structurally intriguing. The API PYR contains an amide and two aromatic nitrogen atoms as synthon handles ( figure 8 a ), and is frequently used in combination with other drugs, which can pose compatibility and bioavailability issues [ 65 ].…”
Section: Co-crystals Involving Pharmaceutical Compoundsmentioning
confidence: 99%
“…S1-S5 of the supporting information. 2013; Lou et al, 2015;Wang et al, 2014Wang et al, , 2015Abourahma et al, 2011;Luo & Sun, 2013;Eddleston et al, 2016;Aree & Chaichit, 2009;Adalder et al, 2012;Aakerö y et al, 2004;Grobelny et al, 2011;Thakuria et al, 2012;Abourahma et al, 2015;McMahon et al, 2005;Thorat et al, 2015). From the structural analysis of the reported cocrystals it was observed that acid-pyridine (synthon I), acid-acid, amideamide and acid-amide dimers (synthon II, III and IV, respectively) are more common for cocrystals of Pyz containing coformers with acid functionality.…”
Section: Pyzá24dhbamentioning
confidence: 99%
“…Fumaric acid was chosen as a bridge to link isoniazid and pyrazinamide as the carboxylic acid functional groups in fumaric acid can interact effectively with N -heterocycles of isoniazid and pyrazinamide to form stronger heterosynthon [ 261 ]. Moreover, the amide functional group of pyrazinamide and hydrazide functional group in isoniazid has been reported to form hydrogen-bonding motifs with dicarboxylic acids and tricarboxylic acids in several studies [ 275 , 276 ]. The selection of suitable dicarboxylic acid plays an important role in determining the success of this ‘drug-bridge-drug ternary cocrystallization strategy’.…”
Section: Ternary and Quaternary Cocrystalsmentioning
confidence: 99%